PENGEMBANGAN KARTU KATA BERBASIS GAME EDUCATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN PEMAHAMAN KOMUNIKASI PADA ANAK USIA DINI: PENGEMBANGAN KARTU KATA BERBASIS GAME EDUCATION UNTUK MENINGKATKAN KEMAMPUAN LITERASI DAN PEMAHAMAN KOMUNIKASI PADA ANAK USIA DINI - Anik anifah; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Game-Based Word Cards for Education to improve literacy skills and communication comprehension for early childhood at Al Falah Assalam Kindergarten in Tropodo Waru. The study used a Research and Development (R&D) approach with the Borg and Gall model, which consists of ten stages, including needs analysis, product design, prototype development, expert validation, limited trials, field trials, and product revision. Validation was conducted by three groups of experts: material experts, design experts, and media experts. The instrument, a questionnaire, assessed the feasibility of the material, visual appeal, and suitability of the use of learning media. The limited trial was conducted on nine respondents (children), and the field trial involved 21 respondents consisting of teachers and students. The aim was to thoroughly test the effectiveness and feasibility of the product in a real-life learning context. The validation results showed a score of 80% from the material experts, indicating that the content was in line with the curriculum. The design experts gave a score of 69–71%, indicating the need for visual improvements. Meanwhile, the media experts assessed the use of Canva as quite effective and appropriate for the characteristics of early childhood. Field trials demonstrated high feasibility with scores of 91–93%, accompanied by positive feedback from teachers and students. Children appeared more enthusiastic and demonstrated improvements in literacy and communication skills. Overall, the Game-Based Educational Word Cards were deemed feasible and effective for use, and have the potential for broader implementation with improvements to the visuals and materials to create fun and interactive learning.